Analisis Kemampuan Berpikir Kreatif Siswa pada Materi Sel Volta dan Sel Elektrolisis dengan Menggunakan Tes Open-Ended Problem - Mohamad, Erni; Iyabu, Hendri; Wiwiyani, Wiwiyani; Sihaloho, Mangara; Bialangi, Nurhayati; Kilo, Akram La (Universitas Negeri Gorontalo, 2023)
This study aims to determine students' creative thinking abilities in the topics of voltaic cells and electrolysis by using open-ended problem tests at SMA Negeri 4 Gorontalo, to understand teachers' responses to the administered open-ended problem tests, and to gauge students' responses to the administered open-ended problem tests. The research approach employed is descriptive qualitative. The subjects of this study were 62 twelfth-grade science students and 2 chemistry teachers at SMA Negeri 4 Gorontalo. The data utilized in the study consist of the results of students' creative thinking ability tests using open-ended problem tests, as well as the responses gathered from questionnaires regarding the test item model. The research findings reveal that students' creative thinking abilities in terms of fluency aspect are at 47.8% categorized as moderately creative, the flexibility aspect at 45.4% categorized as moderately creative, and the originality aspect at 31.9% categorized as less creative. The results from the teachers' questionnaire responses regarding the open-ended problem test model show a positive response rate of 80%, while the results from the students' questionnaire responses indicate a positive response rate of 61%.